2002
DOI: 10.1053/jhep.2002.32148
|View full text |Cite
|
Sign up to set email alerts
|

Acute versus chronic alcohol consumption in acetaminophen-induced hepatotoxicity

Abstract: The aim of this study was to determine by multivariate analysis how alcohol and other factors affect the clinical course and outcome in patients with acetaminophen (paracetamol) poisoning. A total of 645 consecutive patients admitted from 1994 to 2000 with single-dose acetaminophen poisoning were studied, giving special attention to alcohol history, time between overdose and intravenous N-acetylcysteine (NAC) treatment ("time to NAC"), and other data available at the time of admittance. Up until 72 hours after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
153
3
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(163 citation statements)
references
References 45 publications
(61 reference statements)
1
153
3
6
Order By: Relevance
“…Compared with nonabusers, alcohol abusers had lower acetaminophen levels (15 g/dL [range, 0-315] vs. 34 g/dL [0-644]; P ϭ .003), were less likely to use antidepressants (24% vs. 40%; P ϭ .03) or compound narcotics (31% vs. 50%; P ϭ .009), and were less likely to present with severe (grades 3 and 4) hepatic encephalopathy (34% vs. 53%; P ϭ .02). Clinically, there were no other differences between those who were abstinent and those who abused alcohol with regard to INR, ALT, bilirubin, body mass index (BMI), APACHE II score, MELD score, or overall survival (data not shown).…”
Section: Alcohol Use and Abusementioning
confidence: 99%
“…Compared with nonabusers, alcohol abusers had lower acetaminophen levels (15 g/dL [range, 0-315] vs. 34 g/dL [0-644]; P ϭ .003), were less likely to use antidepressants (24% vs. 40%; P ϭ .03) or compound narcotics (31% vs. 50%; P ϭ .009), and were less likely to present with severe (grades 3 and 4) hepatic encephalopathy (34% vs. 53%; P ϭ .02). Clinically, there were no other differences between those who were abstinent and those who abused alcohol with regard to INR, ALT, bilirubin, body mass index (BMI), APACHE II score, MELD score, or overall survival (data not shown).…”
Section: Alcohol Use and Abusementioning
confidence: 99%
“…The smallest reported doses associated with evidence of hepatic injury have ranged from 3.25 to 10 g (2,34-46). A cohort analysis (level 2b) described several patients in whom acute doses of less than 12 g were associated with hepatotoxicity, but the exact doses were not specified (47). This same study reported deaths in patients with reported doses as low as 15 g. In contrast, some reports have described large single ingestions with documented serum concentrations of acetaminophen above the possible or probable toxicity nomogram lines that did not result in toxicity (48).…”
Section: Acute Single Ingestions By Patients 6 Years Of Age and Oldermentioning
confidence: 99%
“…Patients with acute co-ingestion of acetaminophen with alcohol or gastrointestinal antimotility agents and patients taking cimetidine chronically have been reported to be at decreased risk of liver injury (levels 2b and 4) (31,47,50,53,77,78). Other authors have found no correlation between acute alcohol consumption and severity of toxicity (level 2b) (46).…”
Section: Repeated Supratherapeutic Ingestion (Rsti) By Patients 6 Yeamentioning
confidence: 99%
See 2 more Smart Citations